25 Functional Characterization of Genes Mapped in Transmission Ratio Distortion Regions of the Bovine Genome Affecting Reproduction. (10th April 2018) - Fonseca, P A D S; Id-Lahoucine, S; Casellas, J; Miglior, F; Reverter, A; Fortes, M R; Nguyen, L T; Porto-Neto, L R; Sargolzaei, M; Brito, L F; Miller, S P; Schenkel, F S; et al.
Abstract: Transmission ratio distortion (TRD) can be described as the deviation from the expected Mendelian segregation of alleles. Reproduction abnormalities caused by a specific allele or allelic combination may result in violation of Mendel's laws of segregation. Several biological mechanisms can cause TRD, including the preferential transmission of one of the two alleles carried by a heterozygote parent to the zygote at the time of fertilization, embryo or fetal failure and differential viability during early neonatal life. Recently, we developed a Bayesian methodology to identify regions with TRD across the genome using a SNP-by-SNP or haplotype approach. The models can differentiate between parent-unspecific and parent-specific (sire and dam) TRD. Preliminary results using the SNP-by-SNP approach were obtained using 79, 238 Holstein sire-dam-progeny trios, genotyped for 44, 369 autosomal SNP. The number of TRD regions identified were: 270 unspecific TRD regions and 672 parent-specific TRD regions (dam- (n=393) and sire- (n=271) specific TRD). The genes mapped in a 1Mb interval (downstream and upstream) from each one of those regions were annotated in order to perform functional analysis to identify the candidate genes for the phenotypes associated with TRD regions. Additionally, genes associated with puberty and other female fertility traits identified in three independent populations of Brangus, Brahman and Tropical Composite beef breeds were compared with the genes mapped in TRD regions, to confirm the association of these genes with fertility traits. The genes mapped in TRD regions and shared among breeds were annotated in function of a pleiotropic, which evaluated 32 traits in beef cattle. Three genes overlapping in TRD regions and shared among breeds were identified in pleiotropic regions. The IYD, RBM20 and PLA2G4E genes are related with crucial biological processes associated with embryonic development and survival, such as regulation of thyroid metabolism, cardiac muscle development and hydrolization of phospholipids into fatty acids. These genes showed a magnitude of distortion of 0.012, 0.1 and 0.011, with significant TRD, respectively. These genes are relevant positional and functional candidate gens for the phenotypes associated with TRD regions. It is important to highlight that the functional analysis performed here is a very stringent approach. dditional analysis will be conducted to identify other candidate genes in TRD regions and to provide a better characterization of the TRD regions in function of alleles and genes. However, these results indicate that the proposed methodology is able to identify regions with genes involved with crucial biological processes associated with TRD mechanisms.